Pd-Catalyzed carboannulation of γ, δ-alkenyl oximes: efficient access to 5-membered cyclic nitrones and dihydroazines. Issue 3 (3rd January 2019) - Sun, Baozhen; Liu, Shuang; Zhang, Mengru; Zhao, Jinbo; Zhang, Qian
Abstract : The Pd 0 -catalyzed carboannulation of γ, δ-alkenyl oximes with organohalides offers catalyst-controlled access to 5-membered cyclic nitrones or 6-membered cyclic oxime ethers. Abstract : We report that the Pd 0 -catalyzed carboannulation of γ, δ-alkenyl oximes with aryl and vinyl halides offers a straightforward entry path to 5-membered cyclic nitrones or 6-membered cyclic oxime ethers, wherein substrate conformation can result in divergent reactivity, a phenomenon that likely arises from a shift in the mechanistic paradigm. The title transformation features a catalyst-controlled bond formation event that holds promise for the enantioselective synthesis of these important heterocycles.